2022
DOI: 10.3390/ijms232113436
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus sakei MJM60958 as a Potential Probiotic Alleviated Non-Alcoholic Fatty Liver Disease in Mice Fed a High-Fat Diet by Modulating Lipid Metabolism, Inflammation, and Gut Microbiota

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common liver disease with a rapidly increasing number of cases worldwide. This study aimed to evaluate the effects of Lactobacillus sakei MJM60958 (MJM60958) on NAFLD in vitro and in vivo. In in vitro tests, MJM60958 significantly inhibited lipid accumulation by 46.79% in HepG2 cells stimulated with oleic acid and cholesterol (OA-C). Moreover, MJM60958 showed safe and probiotic characteristics in vitro. In the animal study, MJM60958 administration in a high-fat di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…It has been posited previously that the progression of NAFLD could be driven by lipid metabolism disorders ( 2 ). Accumulating evidence suggests that some lactic acid bacteria have the potential to relieve NAFLD ( 13 , 15 ). Our previous studies showed L. acidophilus KLDS1.0901 with antioxidative activity had good tolerance to acid and bile salt and strong adhesion ability ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been posited previously that the progression of NAFLD could be driven by lipid metabolism disorders ( 2 ). Accumulating evidence suggests that some lactic acid bacteria have the potential to relieve NAFLD ( 13 , 15 ). Our previous studies showed L. acidophilus KLDS1.0901 with antioxidative activity had good tolerance to acid and bile salt and strong adhesion ability ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the method of Nguyen et al ( 13 ), 6-week-old male C57BL/6J mice ( n = 24) were obtained from the Vital River Laboratory Animal Technology Company (Beijing, China). Study animals were housed in a sterile animal room at 22 ±0.5°C, 55±5% humidity with 12 h light/12 h dark cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al [29] Acetaminophen overdose and acute alcohol consumption-induced liver oxidative injury…”
Section: Lactobacillus Gasseri (Stain Ckcc1913) Treatmentmentioning
confidence: 99%
“…Subsequently, the same International Scientific Association defined postbiotics as “a preparation of inanimate microorganisms and/or their components that confers a health benefit on the host” [ 90 ]. While the preventive and therapeutic role of probiotics in NAFLD is quite clear in clinical [ 91 , 92 ] and pre-clinical models [ 93 , 94 ], further investigations are needed in patients with MAFLD. A recent meta-analysis showed that the use of probiotics holds promise for reducing liver enzyme levels in patients with MAFLD.…”
Section: Therapeutic Approachesmentioning
confidence: 99%